Legacy of Human Impact on Geomorphic Processes in Mountain Headwater Streams in the Perspective of European Cultural Landscapes - Tomáš Galia (Geosciences, 2021)
Mountain headwater streams are still somewhat on the boundary of interest regarding possible human impact on their morphology or geomorphic processes, which may be caused by our perception of mountains as islands of relatively preserved natural conditions. This paper summarizes the past and present human pressure on the headwater streams that drain the highest mountain ranges of the Outer Western Carpathians in Czechia. Anthropogenic pressure began in this region in the 16th century during a colonization of the mountains and continued by timber harvesting, timber floating, and construction of torrent control works until present. Each of these interventions produced a morphological response of the channels in relation to altered sediment or water fluxes at the whole catchment scale or within longitudinal stream profiles. Because it is highly unlikely to reach pre-settlement conditions of the channels, the management effort should be concentrated to achieve realistic restoration targets under the present socioeconomic circumstances by taking into consideration the morphodynamical specifics of mountain headwater streams.